Nursing Education in the 21st Century: Competencies and Roles of Nursing Instructors - ศรเกษตริน, อติญาณ์; รองเมือง, ดาราวรรณ; จันทรา, รุ่งนภา (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this article is to present the concept of nursing education in 21st century skills of nursing students, competencies and roles of Nursing Instructors. The changing in the 21st century, health care service system and implementing of transformative learning in education require the change in nursing education of the 21st century. Nursing instructors are individuals who have a role in promoting instructional reform to keep up with the changes and having a crucial role in develop the competencies of nursing students by the professional standards established by the Nursing Council as well as the developing of 21st century skills. Therefore, in promoting effective nursing education management for the 21st century, nursing instructors need to be competent and ability to perform their role in various areas as follows: 1) theories and principle of adult learning, 2) curriculum development and implementation, 3) nursing practice, 4) research and evidence, 5) communication, collaboration and partnership, 6) ethical/legal principles and professionalism, 7) monitoring and evaluation, and 8) management, leadership and advocacy.